PERBANDINGAN ALGORITMA SHORTEST PATH DALAM PEMROSESAN CITRA DIGITAL SEAM CARVING - Florentinus Alvin Sebastian; R. Gunawan Santosa; Theresia Herlina R. (Universitas Kristen Duta Wacana, 2016)
Seam carving is a method of content aware image resizing. As solutions shortest path algorithms are used to find images seams. Seam is a horizontal or vertical path of an image that has minimum energy. There are two (2) shortest path algorithms that will be discussed in this paper. This paper contains the results of shortest path algorithms comparison between Dijkstra and Directed Acyclic Graph to see which one is better than another in case of efficiency. The precomputed and recomputed methods will be compared to find the more efficient method for executing the seam carving transformation. A web application has been built for this purpose. This web app is capable of transforming image size with seam carving method. The complexity of Dijkstra and Acyclic will be compared to find which one is better. The result is Dijkstra has been won, with the O(4V) with Acyclicis O(5V). The use of precomputed and recomputed is evaluated by the conditions. If the preparation is evaluated then recomputed is more efficient, but if the preparation is not evaluated then the precomputed method is the better one and has faster performance.